1963
DOI: 10.1002/bip.360010406
|View full text |Cite
|
Sign up to set email alerts
|

The orientation and dissociation field effect of DNA in solution

Abstract: INTRODUCTIONA high electric field may affect the electrolyte conductivity of a polyelectrolyte solution with very long stretched polyions in two different ways. An increase of the conductivity because of increased dissociation is generally observed at high field strengths (dissociation field effe~t).l-~ On the other hand, there is an effect of the field on the mean mobility of the charge carriers which may be noticeable even a t moderate field strengths. Due to polarization of the inner ionic atmosphere of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

1964
1964
2012
2012

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(5 citation statements)
references
References 15 publications
0
5
0
Order By: Relevance
“…The mechanism of DNA orientation is still not well understood. Evidence from dielectric dispersion studies (292,293) and high field denaturation of DNA (294) suggests that the induced dipole moment originates primarily from the migration of ions along the molecular surface. Field reversal experiments (81,286) show that the orientation arises from a field-induced dipole, and transient electric birefringence experiments seem to show that in the absence of a large counterion density the induced dipole moment decreases precipitously (295).…”
Section: Dna-rnamentioning
confidence: 99%
“…The mechanism of DNA orientation is still not well understood. Evidence from dielectric dispersion studies (292,293) and high field denaturation of DNA (294) suggests that the induced dipole moment originates primarily from the migration of ions along the molecular surface. Field reversal experiments (81,286) show that the orientation arises from a field-induced dipole, and transient electric birefringence experiments seem to show that in the absence of a large counterion density the induced dipole moment decreases precipitously (295).…”
Section: Dna-rnamentioning
confidence: 99%
“…The orientation of rod-shaped charged polyelectrolytes under the influence of an electric field has been measured by a number of techniques including electrical birefringence (1-6), electrical conductivity (7,8), and transient electric dichroism (9).…”
Section: Introductionmentioning
confidence: 99%
“…A recent paper considered the effect of an electric field on the electrolyte conductivity in solution (158). Studies on DNA showed that field effects w-ere observable and conformed to theory.…”
Section: Physical Chemistry Of Polyelectrolytesmentioning
confidence: 85%